Outside Caste? The Enclosure of Caste and Claims to Castelessness in India and the United Kingdom. (January 2020) - Mosse, David
Abstract: Caste has always generated political and scholarly controversy, but the forms that this takes today newly combine anti-caste activism with counter-claims that caste is irrelevant or non-existent, or claims to castelessness. Claims to castelessness are, in turn, viewed by some as a new disguise for caste power and privilege, while castlessness is also an aspiration for people subject to caste-based discrimination. This article looks at elite claims to "enclose" caste within religion, specifically Hinduism, and the Indian nation so as to restrict the field of social policy that caste applies to, to exempt caste-based discrimination from the law, and to limit the social politics of caste. It does so through a comparative analysis of two cases. The first is the exclusion of Christian and Muslim Dalits—members of castes subordinated as "untouchable"—from provisions and protections as Scheduled Castes in India. The other case is that of responses to the introduction of caste into anti-discrimination law in the UK. While Hindu organizations in the UK reject "caste" as a colonial and racist term and deploy postcolonial scholarship to deny caste discrimination, Dalit organizations, representing its potential victims, turn to scholarly discourse on caste, race, or human rights to support their cause. These are epistemological disputes about categories of description and how "the social" is made available for public debate, and especially for law. Such disputes engage with anthropology, whose analytical terms animate and change the social world that is their subject.